LANDASAN ILMIAH DAN TEKNOLOGI DALAM PELAYANAN BIMBINGAN DAN KONSELING - Ihsan Nurkholis (Universitas Nasional, 2020)
The development of Science and Technology has a very important role especially in providing access to humans, this can be seen in the industrial revolution that uses machines and technology in doing work. scientific and technological foundations talk about the mistaken nature of guidance and counseling. The scientific and technological foundation in guidance and counseling such as scientific guidance and counseling is a number of logically and systematically arranged knowledge, The role of other sciences and technology in counseling, psychology, education, and counseling, as well as other sciences, guidance development and counseling is based on research.